Mutations Located outside the Integrase Gene Can Confer Resistance to HIV-1 Integrase Strand Transfer Inhibitors - Isabelle Malet (American Society for Microbiology, 2017)
ABSTRACT Resistance to the integrase strand transfer inhibitors raltegravir and elvitegravir is often due to well-identified mutations in the integrase gene. However, the situation is less clear for patients who fail dolutegravir treatment. Furthermore, most in vitro experiments to select resistance to dolutegravir have resulted in few mutations of the integrase gene. We performed an in vitro dolutegravir resistance selection experiment by using a breakthrough method. First, MT4 cells were infected with human immunodeficiency virus type 1 (HIV-1) Lai. After integration into the host cell genome, cells were washed to remove unbound virus and 500 nM dolutegravir was added to the cell medium. This high concentration of the drug was maintained throughout selection. At day 80, we detected a virus highly resistant to dolutegravir, raltegravir, and elvitegravir that remained susceptible to zidovudine. Sequencing of the virus showed no mutations in the integrase gene but highlighted the emergence of five mutations, all located in the nef region, of which four were clustered in the 3′ polypurine tract (PPT). Mutations selected in vitro by dolutegravir, located outside the integrase gene, can confer a high level of resistance to all integrase inhibitors. Thus, HIV-1 can use an alternative mechanism to develop resistance to integrase inhibitors by selecting mutations in the 3′ PPT region. Further studies are required to determine to what extent these mutations may explain virological failure during integrase inhibitor therapy. IMPORTANCE Integrase strand transfer inhibitors (INSTIs) are increasingly used both as first-line drugs and in rescue therapy because of their low toxicity and high efficacy in both treatment-naive and treatment-experienced patients. Until now, resistance mutations selected by INSTI exposure have either been described in patients or selected in vitro and involve the integrase gene. Most mutations selected by raltegravir, elvitegravir, or dolutegravir exposure are located inside the catalytic site of the integrase gene, but mutations outside the catalytic site of the integrase gene have also been selected with dolutegravir. Following in vitro selection with dolutegravir, we report, for the first time, a virus with selected mutations outside the HIV-1 integrase gene that confer resistance to all integrase inhibitors currently used to treat patients, such as raltegravir, elvitegravir, and dolutegravir. Our observation may explain why some viruses responsible for virological failure in patients treated with dolutegravir did not show mutations in the integrase gene.